Laysa Kamithlihi Shay’un: The Interpretation of Mutashābihāt Verses and Traditions by ‘Abd al-Qadir Wangah in Risālah Manhaj Ahl Al-Sunnah - Wan Razali, Wan Mohd Fazrul Azdi; Syed Shamsuddin, Syed Salim; Abdul Aziz, Mohammad Aizuddin; Mohamed, Mohd Faisal (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Among many issues discussed and debated in the field of Islamic theology is the interpretation of the mutashābihāt verses and traditions. Tuan Guru ‘Abd Al-Qadir Wangah, or known as Ayah Dir Sekam, was among the many Malay Muslim scholars who analysed, described and contributed to the proper understanding of mutashābihāt in the Islamic studies. This study aims at analyzing Ayah Dir’s discussion on the interpretation of the mutashābihāt from his writing, namely Risālah Manhaj Ahl al-Sunnah. Textual analysis methodology is applied on this ‘Risālah’ to thematize and organize his main ideas in providing the correct methodology in understanding the mutashābihāt verses and traditions. Findings show that Ayah Dir Sekam’s methodology of interpretation, namely ta’wīl ijmālī and tafṣīlī, is in line with the methodology of classical and modern scholars of Ahl al-Sunnah wa al-Jamā‘ah, which is regarded as the mainstream of Islam. This is due to his strong link with the significant turāth (heritage) and mu‘tabar (credible) writings by these scholars. In the same way, this is also due to his firm educational experience with many well-known Malay Muslim scholars either in the Malay Archipelago or in Mecca.